Bariatric Surgery for Adolescents with Type 2 Diabetes: An Emerging Therapeutic Strategy - Stefater, MA (Curr Diab Rep, 2017)
PURPOSE OF REVIEW: Type 2 diabetes (T2D) is a growing public health problem in youth, but conventional treatments are often insufficient to treat this disease and its comorbidities. We review evidence supporting an emerging role for bariatric surgery as a treatment for adolescent T2D. RECENT FINDINGS: Paralleling what has been seen in adult patients, bariatric surgery dramatically improves glycemic control in patients with T2D. In fact, remission of T2D has been observed in as many as 95–100% of adolescents with diabetes after bariatric surgery, particularly vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) surgery. This striking outcome may be due to both weight-dependent- and weight-independent factors and recent studies suggest T2D-related comorbidities may also improve after surgery. SUMMARY: Bariatric surgery including RYGB and VSG is a powerful therapeutic option for obese adolescents with T2D. Benefits must be weighed against risk for postoperative complications such as nutritional deficiencies, but earlier surgical intervention might lead to more complete metabolic remission in obese patients with T2D.